2016
DOI: 10.5897/ajmr2015.7645
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of putatively toxigenic Aspergillus species in maize and soil samples in an aflatoxicosis hotspot in Eastern Kenya

Abstract: Aflatoxin contamination impinges on grain quality worldwide. The causative agent, Aspergillus spp. colonizes grain in the field down to postharvest stages in storage where they may produce toxins. Kenya has experienced recurring cases of aflatoxicosis in Eastern region especially during periods of maize grain deficit. The risk of chronic exposure has not been widely studied. Therefore, seasonal variation in abundance and species composition of toxigenic Aspergillus in maize and soils of Eastern Kenya was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Frequency of isolation was assessed as the number of times every isolate has appeared per site sampled. As described by; (Benard et al, 2013) using the following equation;…”
Section: Assessment Of Diversity and Frequency Of Isolationmentioning
confidence: 99%
“…Frequency of isolation was assessed as the number of times every isolate has appeared per site sampled. As described by; (Benard et al, 2013) using the following equation;…”
Section: Assessment Of Diversity and Frequency Of Isolationmentioning
confidence: 99%
“…Three strains of Aspergillus avus and three strains of Fusarium sp. were obtained from the Mycotoxin Research Laboratory at Egerton University, Nakuru Kenya (Elsie et al 2016). These fungal strains had originally been isolated from contaminated soils and stored as pure cultures in Potato Dextrose Agar (PDA) at 25°C.…”
Section: Fungal Strains and Inoculamentioning
confidence: 99%
“…parasiticus . For example, studies in Kenya showed that the density of A. flavus in soil was higher than that of A. parasiticus (Benard et al, 2013;Elsie et al, 2016). This is the opposite with the Zambian scenario ((Kachapulula et al, 2017b); Figure 3), which has a different climate and is at higher latitude than Kenya.…”
Section: Comparison Of Soil and Maize Community Structuresmentioning
confidence: 96%
“…Soil is the main reservoir for Flavi . Flavi communities on crops and in soil have been explored before Elsie et al, 2016;Thathana et al, 2017). Considering that soil is a niche for mycotoxigenic Flavi that may infect crops growing on those soils, Aspergillus biocontrol agents (non-aflatoxin producing isolates of Aspergillus flavus) are generally applied to the soil, to outcompete mycotoxigenic strains after transfer to the crop.…”
Section: Supplemental Materialsmentioning
confidence: 99%